Coccinia grandis Extract Exerts Antihyperglycemic Effect through its Antioxidant, α-Amylase and α-Glucosidase Inhibitory Activities: An in vitro Study - Packirisamy, Meenatchi; Sivaprakasam, Maneemegalai (Asian Journal of Biological and Life Sciences)
An increasing demand for herbal medicines has shifted the attention from synthetic to natural antioxidants and antidiabetic agents. In this study, the edible plant Coccinia grandis fruits (CGF) were assessed for radical scavenging and antioxidant potentials based on NO (nitric oxide) radical scavenging activity, ABTS- [(2,2’-Azino-bis(3-ethylbenzothiazoline- 6-sulfonic acid) diammonium salt] and FRAP- Ferric reducing antioxidant power. In vitro a-amylase and α-glucosidase inhibitory activities were evaluated by using porcine pancreatic α-amylase and yeast α-glucosidase, respectively. The results from free radical scavenging and antioxidant tests clearly indicated the concentration dependent free radical scavenging and antioxidant activities. The extract exhibited the best inhibitory activities against a-amylase and a-glucosidase with IC50 (half maximal inhibitory concentration) values of 117.64± 4.54 μg/mL and 81.6 ± 3.64 μg/mL, respectively. These data suggest that the possible mechanisms underlying antihyperglycemic activity of C. grandis extract, presumably by its radical scavenging/antioxidant activities and through inhibition of α- amylase and α-glucosidase. This study also provides scientific evidence to corroborate the efficacy of this plant as an alternative antidiabetic agent.
Keywords: a-amylase; Antioxidant; Coccinia grandis; Diabetes mellitus; α-glucosidase